Trust as a Mediator in the Relationship between Islamic Fintech Acceptance, User Experience, and Financial Satisfaction - Arif Ikhsan Nurfaizy; Muhammad Sholahuddin (Jurnal Economic Resource, 2026)
The swift expansion of Sharia-compliant financial technology has expanded access to Islamic financial services. However, successful adoption relies as much on consumers' trust as on technology and experience. This quantitative explanatory research examines the mediating role of trust in Islamic fintech between technology acceptance and user experience satisfaction, and between user experience satisfaction and financial satisfaction. Data were collected from 236 active users via structured questionnaires and analyzed using PLS-SEM with SmartPLS 3.0, including outer-model evaluation (validity and reliability tests) and inner-model evaluation (R-square, Q-square, and hypothesis testing via bootstrapping). Results show that technology acceptance and user experience satisfaction positively and significantly influence trust, and trust significantly enhances financial satisfaction. Moreover, the impact of trust on financial satisfaction is partially mediated by technology acceptance. The findings provide both theoretical and practical implications: theoretically, this study strengthens the integration of the Technology Acceptance Model (TAM) with trust in the context of Islamic fintech, while, practically, it offers strategic insights for service providers to enhance user trust, improve system usability, and ultimately increase users’ financial satisfaction